Surat Kuasa dan Gugatan (Analisis Konsep dan Teknik Penulisan) - Syahrul Sitorus (Hikmah, 2020)
Power of attorney and lawsuit are two things that are inseparable when an Advocate carries out his profession to defend the legal interests of his client, especially in civil cases in court, so it can be said that these two things are the heart of handling civil cases that an Advocate must really understand. In formulating a power of attorney and a lawsuit an Advocate is required to understand the formal and material laws of the case he is handling, in addition to that Advocates are required to understand the legal construction of the case being handled by an Advocate, without understanding the above it is very difficult to narrate the minutes of the power of attorney and lawsuit in the said case. Understanding in formulating a power of attorney and lawsuit is the basic capital of a prospective Advocate before carrying out the Advocate profession, so that the Advocate Organization makes this an object of examination for prospective Advocates in the Advocate Professional Exam to assess whether the prospective Advocate is eligible to be appointed as an Advocate being appointed as an Advocate by the Advocate Organization but unable to formulate a power of attorney and lawsuit, of course this is very detrimental to the justice-seeking community in general.